A Review of Population Pharmacokinetic Models of Posaconazole - Ding Q; Huang S; Sun Z; Chen K; Li X; Pei Q (Dove Medical Press, 2022)
Qin Ding,1,* Shuqi Huang,1,* Zexu Sun,2 Kaifeng Chen,1 Xin Li,3 Qi Pei1 1Department of Pharmacy, The Third Xiangya Hospital, Central South University, Changsha, People's Republic of China; 2Xiangya School of Pharmaceutical Sciences, Central South University, Changsha, People's Republic of China; 3Department of Hematology, The Third Xiangya Hospital, Central South University, Changsha, People's Republic of China*These authors contributed equally to this workCorrespondence: Qi Pei, Department of Pharmacy, The Third Xiangya Hospital, Central South University, Changsha, 410013, People's Republic of China, Tel +86 1 317 041 9804, Email peiqi1028@126.com Xin Li, Department of Hematology, The Third Xiangya Hospital, Central South University, Changsha, 410013, People's Republic of China, Email lixiner1975@163.comAbstract: Posaconazole is often used for the prophylaxis and treatment of invasive fungal infections (IFI). However, intra- and inter-individual differences and drug interactions affect the efficacy and safety of posaconazole. Precision dosing of posaconazole based on the population pharmacokinetic (PopPK) model may assist in making significant clinical decisions. This review aimed to comprehensively summarize the published PopPK models of posaconazole and analyze covariates that significantly influence posaconazole exposure. Articles published until May 2022 for PopPK analysis of posaconazole were searched in PubMed and EMBASE databases. Demographic characteristics, model characteristics, and results of PopPK analysis were extracted from the selected articles. In addition, the steady-state pharmacokinetic profiles of posaconazole were simulated at different covariate levels and dosing regimens. Out of the 13 studies included in our review, nine studies included adults, three included children, and one included both adults and children. All oral administration models were one-compartment models, and all intravenous administration models were two-compartment models. Body weight, proton pump inhibitors, and incidence of diarrhea were found to be important covariates. Clinically, the potential impact of factors such as patient physiopathologic characteristics and comorbid medications on posaconazole pharmacokinetics should be considered. Dose adjustment in combination with TDM or replacement with a tablet or intravenous formulation with higher exposure may be an effective way to ensure drug efficacy as well as to reduce fungal resistance. Meanwhile, published models require further external evaluation to examine extrapolation.Keywords: posaconazole, population pharmacokinetics, nonlinear mixed effects modeling, therapeutic drug monitoring